Content Analysis of Religious Articles in the Opinion Column in the Palopo Pos Daily Newspaper - Ria Amelinda (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this article is to describe the standard content of religious articles required by the daily newspaper Palopo Pos, and the contents of religious articles submitted by the author of the article in the opinion column in the daily newspaper Palopo Pos. The type of research is classified as qualitative with the research approach used are: linguistic approach, journalistic approach and da'wah approach. The data source for this research is the daily newspaper Palopo Pos and other sources in the form of literature, both related to journalism and linguistics. Furthermore, the data collection method used is documentation and reference tracing. Then processing techniques and data analysis were carried out using content analysis theory by Ole. R. Holsti. According to him, content analysis is used to answer the questions